Pendidikan Nilai-Nilai Religiusitas dan Kecerdasan Adversitas Pada Era Revolusi Industri 4.0 di Madrasah Mu’allimaat Muhammadiyah Yogyakarta Indonesia - Sutarman (STAI Terpadu Yogyakarta, 2019)
This study aims to find out the deep on the education in Madrasah Mu'allimaat Muhammadiyah Yogyakarta which covers: (1) education on spiritual quotient; (2) education on adversity quotient; and (3) the implication of the spiritual quotient and the adversity quotient education for the students. This research is qualitative research through descriptive qualitative. Research subjects taken as the sample are:a) Madrasah stakeholders; and b) Students. The results of this study shows: (1) the transformation of religiosity values; (2) the transformation of adversity quotient values:a) students be patient, that is refraining when facing the problems and trying to find solution; b) be optimistic and have a resilient spirit.